Antibacterial drug releasing materials by post-polymerization surface modification - Chng, S; Moloney, M; Wu, L (World Scientific Publishing, 2017)
Functional materials are available by the post-polymerization surface modi¯cation of diverse polymers in a three-step process mediated, ¯rstly, by carbene insertion chemistry, secondly, by diazonium coupling, and thirdly by modi¯cation with a remotely tethered spiropyran unit, and these materials may be used for the reversible binding and release of Penicillin V. Surface loading densities of up to 0.19 mmol/g polymer are achievable, leading to materials with higher loading densities and release behavior relative to unmodi¯ed controls, and observable antibacterial biocidal activity.